2015
DOI: 10.1039/c4nr05486e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and optical properties of GaAs/InGaAs/GaAs nanowire core–multishell quantum well heterostructures

Abstract: GaAs/InGaAs/GaAs nanowire core-multishell heterostructures with a strained radial In0.2Ga0.8As quantum well were fabricated by metal organic chemical vapor deposition. The quantum well exhibits a dislocation-free phase-pure zinc-blende structure. Low-temperature photoluminescence spectra of a single nanowire exhibit distinct resonant peaks in the range from 880 to 1000 nm, corresponding to the longitudinal modes of a Fabry-Pérot cavity. This suggests a decoupling of the gain medium and resonant cavity so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…For example, surface-passivated core-shell NW heterostructure can dramatically enhance the emission efficiency and electron mobility [ 5 7 ]. In comparison with homogeneous NWs, NW core-multishell quantum well (QW) heterostructures are more attractive in nanolasers due to the much stronger carrier confinement, decoupled cavity/gain-medium structure, as well as wavelength tenability [ 8 10 ]. However, due to the lattice mismatch between different materials, dislocations may generate in the NW heterostructures, which dramatically degrade the performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, surface-passivated core-shell NW heterostructure can dramatically enhance the emission efficiency and electron mobility [ 5 7 ]. In comparison with homogeneous NWs, NW core-multishell quantum well (QW) heterostructures are more attractive in nanolasers due to the much stronger carrier confinement, decoupled cavity/gain-medium structure, as well as wavelength tenability [ 8 10 ]. However, due to the lattice mismatch between different materials, dislocations may generate in the NW heterostructures, which dramatically degrade the performance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, InGaAs/GaAs QW nanowires have been successfully grown and show good potential in optoelectronic applications. 9, 30 However, no attempts have been made on GaAs1-xSbx QW nanowires. In addition, the lateral growth behavior of GaAs1-xSbx has yet to be explored compared with their axial counterparts.…”
mentioning
confidence: 99%
“…29 Thus, the growth of III-V QW nanowires has been extensively studied in the InGaAs/GaAs, GaAs/Al1-yGayAs, InGaAs/InP, InAs/InP, InAsP/InP, InGaN/GaN material systems. 24,27,[30][31][32][33] Unfortunately, growing high quality and uniform QW around the nanowire remains extremely challenging due to the anisotropic crystal growth and composition inhomogeneity. 34,35 As a consequence, lasing has only been demonstrated to date in InGaN/GaN and GaAs/Al1-yGayAs QW nanowires.…”
mentioning
confidence: 99%
“…The advantage of our approach is that several single NWs grown on the same substrate can be measured in the as-grown geometry. This makes it possible to study the structural parameters among different single NWs and correlate observed deviations with additional physical measurements such as photoluminescence or cathodoluminescence wavelengths and intensities taken from the same NWHS (Yan et al, 2015;Ahtapodov et al, 2012;Rigutti et al, 2011). As already shown by Biermanns et al (2009), individual GaAs NWs grown on the same substrate may exhibit different structural parameters.…”
Section: Introduction and Objectivesmentioning
confidence: 93%